Pengembangan Media Pembelajaran 3D Berbasis Microsoft Powerpoint Materi the Earth and Beyond Kelas V - Purba, Hengky Tantri Badakara; Kartono, Kartono; Ghasya, Dyoty Auliya Vilda (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
This research aims to develop relevant innovations in the form of 3D Learning Media on The Earth and Beyond material that are appropriate, effective, and get good responses from students for use in class V SDS Adicita Mulia Pontianak. This study uses the ADDIE development model which includes 5 steps, namely: Analysis, Design, Development, Implementation, Evaluation with a mixed method approach. The test subjects in this study were V grade students at the Adicita Mulia Pontianak Private Elementary School, with a total of 23 students. The results of the Research on the Development of 3D Learning Media are categorized as